TRANSFORMATIONS OF THE IMAGE OF CLEOPATRA VII, QUEEN OF EGYPT. BETWEEN HISTORICAL NARRATIVE AND POPULAR CULTURE - Kulpa, Karolina (Studia Europaea Gnesnensia, 2017)
Transformations of the image of Cleopatra VII, Queen of Egypt. Between historical narrative and popular culture